Sustainable development - an introduction - Choudhary, Chiranjiv et al. (2003)
This paper introduces the subject of sustainable development. It examines the various definitions of the term as enunciated by international and national development organizations. It posits that there are some basic ecological constraints governing the process of development. The goals of sustainable development in India are discussed. The paper then proceeds to discuss the scenario in the population, agriculture and forestry sectors in detail. - Reproduced.
Keywords: Sustainable development